2020
DOI: 10.4314/jae.v24i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relative pricing of alternative cooking energy sources on their substitution between rural and urban households in Enugu State, Nigeria

Abstract: This study investigated the effects of relative pricing of alternative cooking energy sources on their substitution. The study was conducted in Enugu State Nigeria using primary data collected from two hundred and four households from rural and urban areas of the state, using structured questionnaires. The information collected were pattern and levels of energy use, relative pricing of alternative energies and energy substitution pattern. Data were analyzed using multiple regression analysis and Chow test. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Southeastern geopolitical region of Nigeria is one of the six geopolitical zones in the country. It comprises five states -Imo, Enugu, Ebonyi, Anambra, and Abia (Onyekuru et al, 2020). The region is characterized by a tropical monsoon climate (Onyekuru et al, 2020).…”
Section: Study Area and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Southeastern geopolitical region of Nigeria is one of the six geopolitical zones in the country. It comprises five states -Imo, Enugu, Ebonyi, Anambra, and Abia (Onyekuru et al, 2020). The region is characterized by a tropical monsoon climate (Onyekuru et al, 2020).…”
Section: Study Area and Datamentioning
confidence: 99%
“…It comprises five states -Imo, Enugu, Ebonyi, Anambra, and Abia (Onyekuru et al, 2020). The region is characterized by a tropical monsoon climate (Onyekuru et al, 2020). The region lies between latitude 23° 27′ north to 23° 27' South, with an average rainfall of between 2,000 and 3,000 mm (118.1 in) per year (Onyekuru et al, 2020).…”
Section: Study Area and Datamentioning
confidence: 99%
“…Literature search and review of scholarly papers on Scopus database focusing on improved cookstoves and clean cooking fuels transition in Nigeria shows that economics and perception based literature lead the way. Many of the studies focused mainly on behavior change techniques, role of social perception, cultural norms, and habits, price and other socio‐demographic factors 10–21 but largely ignored the role of economic agents such as cooperatives, credit institutions and other factors in the transition to clean cooking. Also, the focus of many existing is not southeast Nigeria, which is also experiencing high rate of deforestation resulting from cooking with fuelwood.…”
Section: Introductionmentioning
confidence: 99%
“…Chukwu (2001) observed that over 70% of the total population of Nigeria relies on fuelwood or charcoal as their major source of energy for cooking and heating purposes. International Food Policy Research Institute (IFPRI) publication (Onyekuru, 2008) indicated that about 50% of Nigeria's total energy consumed for agriculture and other domestic food processing activities came from fuel wood.…”
Section: Introductionmentioning
confidence: 99%
“…There is the likelihood that sooner than later, supply sources would not cope with demand and the business would suffer (Abah and Ochonu, 2018) One of the reasons that traditional energy source is the preferred domestic fuel is that it does not require a complex and expensive infrastructure to be produced and used as a fuel. Furthermore, so far it is the cheapest (usually free) available energy resource for the rural population and urban poor (Onyekuru, 2008). According to Yahaya (2002), there exists a direct relationship between human population and fuel wood demand, hence, the cutting down of wet wood can be said to be on the increase.…”
Section: Introductionmentioning
confidence: 99%